Macromolecular derivatives of methotrexate and ferrocene as potential prodrugs in cancer chemotherapy - Mufula, Ilunga (My University, 2010)
Cancerous diseases present a formidable health problem worldwide. While the chemotherapy of cancer, in conjunction with other treatment modalities, has reached a significant level of maturity, efficacious use of such agents is still restricted by numerous pharmacological deficiencies, such as poor solubility, short serum circulation lifetimes, and low bioavailability resulting from lack of affinity to cancer tissue and inadequate mechanisms of cell entry. More critically still, most drugs suffer from toxic side effects and a risk of drug resistance. In an attempt to enhance the therapeutic effectiveness of carcinostatic drugs, the concept of anchoring bioactive agents to polymeric carriers has proved to be a promising approach to overcome these deficiencies and was the main aim of this project. Water-soluble, biodegradable macromolecular carriers used were polyaspartamides, prepared by an aminolytic ring-opening process of polysuccinimide; polyamides obtained by ester-amine base-catalyzed polyaddition; and polyamidoamines prepared by Michaeltype addition polymerization. The drug-anchoring potential of carrier polymers was demonstrated by the coupling of methotrexate (MTX), ferrocene and platinum drug models. MTX was linked to carrier via polymer attached amine by N-acylation of linear aminefunctionalized polyaspartamide carriers with the acid group from methotrexate. Acylation was brought about by mediation of HBTU coupling agent. The resulting MTX content of the conjugates was in the range of 10-19% by mass. In the present dissertation, series of water-soluble ferrocene conjugates were synthesized as for MTX by N-acylation of linear amine-functionalized polyaspartamide carriers with 4-ferrocenylbutanoic acid. Acylation was brought about again by mediation of HBTU coupling agent. The resulting iron content of the conjugates was in the range of 6-13% by mass. Polymer-attached dihydroxylato-type ligands were used to anchor the platinum drug to the polymeric carriers. The platinum content of the conjugates was in the range of 6-8% by mass. A member of selected conjugates was submitted to the Department of Immunology, University of Pretoria, and to the School of Pharmacy, University of California, Los Angeles, CA, for biomedical activity assessment. In order to demonstrate the multidrug-binding capacity of the polyaspartamide-type carriers, ferrocene was co-conjugated to selected polymeric conjugates containing MTX or folic acid. The latter was used to ensure target-specific drug delivery.